Production and Evaluation of a Purified Adenovirus Group-Specific (Hexon) Antigen for Use in the Diagnostic Complement Fixation Test - Dowdle, W. R. (1971)
A simple procedure for the production of large volumes of purified adenovirus group-specific complement-fixing (CF) (hexon) antigen by selective adsorption to and elution from CaHPO(4) is described. Results of immunodiffusion tests, electrophoresis, electron microscopy, and tests for hemagglutination and infectivity indicate that the purified antigen consisted of a single virus component (hexon). The purified product contained little host materials. Unlike the crude virus harvest usually employed for serodiagnostic CF tests, the purified antigen demonstrated no anticomplementary activity and did not develop such activity during storage. The purified antigen was equal to or slightly more sensitive than crude virus harvests for serodiagnosis of adenovirus infections.